Shock corridor [videorecording (DVD)] - Fuller, Samuel, 1912-1997; Breck, Peter; Towers, Constance; Evans, Gene, 1922-1998; Best, James, 1926-2015; Rhodes, Hari (Criterion collection, 1998)
A journalist gets himself admitted to a mental hospital to solve the murder of an inmate.